Greenhouse Gas Mitigation Opportunities in Agricultural Landscapes : A Practitioner’s Guide to Agricultural and Land Resources Management - Braimoh, Ademola K. (World Bank, Washington, DC, 2016)
Agriculture, and the patterns of land-use change that are associated with it, have a significant ecological footprint, including the effects it has on climate change, accounting for about one-quarter of anthropogenic greenhouse gas (GHG) emissions globally. Yet agriculture is also the only economic sector in which opportunities are present to mitigate climate change, mainly by removing substantial volumes of carbon from the atmosphere and sequestering them in soils and plant tissues. This report synthesizes information on the many areas in which agricultural GHG emissions can be reduced. Its focus is on mitigation, though many if not most of the measures described address adaptation and resilience as well. The three pillars of CSA serve two purposes in this respect, which is highly appropriate because we can never take our eyes off the imperative of increasing productivity and employing agriculture as an instrument for economic development. The report highlights the pattern of emissions in agricultural landscapes and the primary sources of these emissions. Thereafter, it reviews mitigation opportunities in croplands, pastures, livestock, soil management, biofuels, and elsewhere, followed by case studies that illustrate practical examples. These practical lessons are useful in contributing to the knowledge base of good practices. The report then turns to the factors that constrain or enable the uptake of climate-smart solutions, such as those depicted in the case studies, and discusses ways to overcome the constraints and elements of enabling environments in which mitigation alternatives become widely embraced. The final exercise feeding into the report is a review of Nationally Determined Contributions (NDCs)—an outline of country- level strategies to address climate change. This also presents recommendations for prioritizing World Bank (Bank) mitigation engagement in each region. Approaches to filling mitigation financing and knowledge gaps in country programs, boost the Bank’s mitigation investment portfolio, and create a cohesive strategy for implementing mitigation technologies and practices are discussed.